IDENTIFIKASI VARIETAS KENTANG â€œSUPERJOHNâ€ BERDASARKAN PENANDA RAPD (Random Amplified Polymorphic DNA) - Runtunuwu, David S.; Rogi, J. E.X.; Palendeng, J. H. (EUGENIA, 2011)
ABSTRACT Identification using morphological characters has time consuming. Currently, identification using molecular markers has now been popular due to rapid, saving time and more precisely. Superjohn potato variety has been cultivated in North Sulawesi. However, the Superjohn potato variety has not been characterized using molecular markers. This research was aiming to identify â€œSuperjohnâ€ potato based on RAPD (Random Amplified Polymorphic DNA) markers. The research was conducted in field and laboratory. Field research was performed by taking some young leaves from â€œSuperjohnâ€, Granola, and Atlantic variety from the field. Identification using molecular marker was conducted at laboratory.Â  Nine RAPD primers were used to identify the superjohn variety. The nine primers were OPA-1, OPA-2, OPA-3, OPA-4, OPA-5, OPA-7, OPA-9,Â  OPA-10, andÂ  OPO-1.Â  The molecular identification revealed that â€œSuperjohnâ€ variety was different with Granola and Atlantic. OPA-9700 primer could be used for identificationÂ  â€œSuperjohnâ€ variety while OPA-101000 primer was suitableÂ  for identificationÂ  Granola variety. Keywords:Â  Potatoes, variety, â€œSuperjohnâ€, Granola, Atlantic, and RAPD ABSTRAK Penelitian ini dilakukan untuk mengidentikasi kentang â€œSuperjohnâ€ berdasarkan penanda RAPD (Random Amplified Polymorphic DNA).Â  Penelitian dilakukan di lapangan dan laboratorium. Penelitian lapangan dilakukan dengan mengambil beberapa daun muda dari varietas kentang â€œSuperjohnâ€, Atlantik dan Granola. KemudianÂ  analisis DNA dilakukan di laboratorium menggunakan analisis RAPD. Berdasarkan penanda RAPD ternyata kentang â€œSuperjohnâ€ berbeda dari kentang Granola dan kentang Atlantik. Penanda RAPD OPA-9700 dapat digunakan untuk mengidentifikasi kentangâ€œSuperjohnâ€ dan penanda RAPDÂ  OPA-101000 dapat digunakanÂ  untuk mengidentifikasi kentang Granola. Kata kunci: Â Kentang,Â  varietas, Superjohn, Granola, Granola, RAPD